Art and Autobiography: A Study of the Self in Literature - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
In this paper, I have attempted to apply critical approaches of William C. Spengemann to study Oscar Wilde’s Salomé as an autobiographical work that involves a set of assumptions such as biographical information about the author and information about the work’s genesis, which should be given the secondary importance. Instead of the idea of defining autobiography as self-written biography, it is necessary to understand the ways in which different autobiographers write in different forms and at different times. So the main purpose of this paper is to explore the self in literature, i.e. Wilde’s Salomé. Essentially, how can a piece of literary work be considered as an autobiography that has been practiced in response to shifting ideas about the nature of the self?Crossing the Border: International Journal of Interdisciplinary Studies Vol.4(1) 2016: 19-28